Dry sliding wear behavior of treated AISI 304 stainless steel by gas nitriding processes. (2021) - Ramya Sree, K.; Reddy, G. Keerthi; Prasanna, G. Lakshmi; Saranya, J.; Anitha Lakshmi, A.; Swetha, M.; Vineeth Raj, T.; Subbiah, Ram
Abstract: The wear behaviour of AISI 304 stainless steel was investigated at consistent load. For gas nitriding the specimen were placed on top of alumina block and ammonia gas was allowed to flow through quartz tube at a flow rate of 100 ml/min, temperature of 570 °C and were treated at different nitriding timings like Gas nitriding 1 (GN1 ) 6 h, Gas nitriding 2 (GN2 ) 12 h, and Gas nitriding 3 (GN3 ) 18 h. After heat treatment wear test was done to find out the wear loss in the material. The pin of 40 mm length and 12 mm diameter was held on rotating disc of 150 mm diameter. The wear test for all specimens was conducted under the normal loads of 20 N and 30 N respectively. Metallographic tests like optical microscopic results, SEM is done to specimens for comparing physical characteristics before and after heat treatments. To compare the mechanical characteristics of the heat treated specimens before and after heat treatments they are subjected to pin on disc experiment and Vickers hardness test to determine wear resistance and hardness of the material. From SEM analysis, it was observed that a decomposition of CrN layer in the gas nitride specimen for 18 h. It was concluded that nitride distribution increases with increase in nitriding time. The hardness of gas nitride specimen3 (18 h) was found to be 1187 HV and the hardness for untreated specimen was found to be 330 HV .